2002
DOI: 10.1159/000063104
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Anemia in Hemodialysis Patients Treated by Hemodiafiltration with High-Volume On-Line-Prepared Substitution Fluid

Abstract: Background: Hemodiafiltration (HDF) is associated with a lower incidence of neuropathy, carpal tunnel syndrome, joint pain, and partial correction of anemia. HDF with on-line-prepared substitution fluid (OL HDF), as compared with conventional hemodialysis, increases the treatment tolerance and, as compared with standard HDF, avoids storage problems and allows a higher substitution volume at low cost. Methods: Thirty-two hemodialysis patients treated by OL HDF for at least 9 months were studied. Hemoglobin, hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
4
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 22 publications
2
63
4
6
Order By: Relevance
“…An improved response to erythropoietin has been reported in two observational studies of patients who were treated by on-line hemodiafiltration with conventional high-flux membranes (50,51), although the finding was not confirmed in a randomized, controlled study (52), and there is the potentially confounding effect of ultrapure dialysate to consider (31). A preliminary report also suggested that plasma total homocysteine concentrations may be normalized with a combination of on-line hemodiafiltration and vitamin supplementation (53).…”
Section: Can Protein-leaking Membranes Have An Impact On Uremic Toxinmentioning
confidence: 99%
“…An improved response to erythropoietin has been reported in two observational studies of patients who were treated by on-line hemodiafiltration with conventional high-flux membranes (50,51), although the finding was not confirmed in a randomized, controlled study (52), and there is the potentially confounding effect of ultrapure dialysate to consider (31). A preliminary report also suggested that plasma total homocysteine concentrations may be normalized with a combination of on-line hemodiafiltration and vitamin supplementation (53).…”
Section: Can Protein-leaking Membranes Have An Impact On Uremic Toxinmentioning
confidence: 99%
“…In the interim, several studies have used surrogates such as assessment of nutrition, phosphate control, and erythropoietin requirements in patients treated by haemodiafiltration and haemodialysis. Although some studies have reported an improvement in nutritional parameters [7,8], serum phosphate control [9,10] and response to erythropoietin [11,12] with on-line haemodiafiltration, these have not been universal findings with other studies reporting no benefit [2], particularly when smaller volumes of ultrafiltration [13] or regenerating sorbent techniques were used [14]. …”
Section: Introductionmentioning
confidence: 99%
“…G. Bonforte с со-авт. свидетельствуют о достоверном снижении дозы эритропоэтина через 12, 18 и 24 месяца после пере-вода пациентов с СТГД на ОЛ-ГДФ [26]. По данным C. Lin с соавт.…”
Section: снижение потребности в медикаментах -лечение анемииunclassified